Pacifying the Crises of (Un)Constitutional Amendments: The Case of Zimbabwe’s Amendment (No.1) and (No.2) Acts - Matanda, Tonderai (Strathmore Law Review, 2022)
Zimbabwe enacted a new constitution in 2013 amid high hopes for a turn towards a new era of democratisation, constitutionalism, and adherence to the rule of law. However, subsequent to 2013, Zimbabwe entered an era of regression on the democratic values espoused by the new constitution. The apogee of the regression is the amendments of the Constitution, neutralising some of its most progressive elements. This paper analyses two recent constitutional amendments: amendments no. 1 and no.2, in the Zimbabwean context pertaining to judicial appointments and terms of office. It also evaluates the potential of judicial review of substantive validity of constitutional amendments through the lens of the doctrine of ‘unconstitutional constitutional amendments’. This is in defence of core constitutional values such as equal protection of the law, rule of law, separation of powers, and democratic participation. The central argument of this paper is that the amendments, which contravene the values espoused by the Constitution, are substantively unconstitutional because they precipitate a multi-pronged crisis of constitutionalism. These crises are embodied in the indirect control of the judiciary by the executive, and in ‘rule by law’ replacing ‘rule of law’. This article proposes that these crises can be remedied by exploring the doctrine of unconstitutional constitutional amendments.